Respuesta :

Explanation

We are given the following functions:

[tex]\begin{gathered} P(x)=6x \\ Q(x)=2x^3+3x^2+1 \end{gathered}[/tex]

We are required to determine the following:

[tex]P(x)\cdot Q(x)[/tex]

This is achieved thus:

[tex]\begin{gathered} P(x)=6x \\ Q(x)=2x^3+3x^2+1 \\ \\ \therefore P(x)\cdot Q(x)=(6x)(2x^3+3x^2+1) \\ P(x)\cdot Q(x)=6x\cdot2x^3+6x\cdot3x^2+6x\cdot1 \\ P(x)\cdot Q(x)=12x^4+18x^3+6x \end{gathered}[/tex]

Hence, the answer is:

[tex]\begin{equation*} 12x^4+18x^3+6x \end{equation*}[/tex]